Mandat dan Fungsi dari Komisariat Tinggi PP Urusan Pengungsi (UNHCR) - Jaquemet, Stephane (Indonesian Journal of International Law, 2004)
The article highlights and describes the main aspects of the mandate of the United Nations High Commissioner for Refugees (UNHCR), in particular its operational dimension which has mainly been built as a worldwide response to refugee crises, and its protection role, which entails all activities aimed at ensuring that the rights of refugees and other persons of concern are respected and promoted by States. In the second part of the article, the author summarizes UNHCR’s activities, both present and past in Indonesia.